APPLICATION OF THE IMMUNOCHROMATOGRAPHIC TEST KIT FOR SEROLOGICAL DIAGNOSIS OF BRUCELLOSIS BASED ON RECOMBINANT ANTIGEN - Manat Е.; Sarina , N.I.; Eskendirova , S.Z.; Shustov , A.V.; Mukanov , K.K. (Eurasian Journal of Applied Biotechnology, 2016)
Despite the significant progress jointly made by scientists and practical veterinary service in the Republic of Kazakhstan, the problem of animal brucellosis has not been completely solved. Consistently high levels of human brucellosis morbidity, which is due to extremely tense epizootic situation and large socio-economic damage, determine the special importance of this infection in the structure of infectious pathologies. One of the potential to increase the sensitivity and specificity of serological diagnostic methods of brucellosis is the use of recombinant analogs of immunodominant proteins of pathogenic Brucella, which diversity has determined and studied at the present time. Periplasmic protein BP26 is a specific antigen which is highly conserved for genus of Brucella. It has high diagnostic value for use in the development of immunoassays and immunochromatographic test kits of brucellosis for the veterinary and medical use. A highly sensitive and specific immunoassay system for rapid detection of antibrucellar antibodies was developed on the basis of recombinant Brucella antigen BP2. It is intended for serological diagnosis of brucellosis in animals. High diagnostic efficiency of ICA was tested in 962 samples of blood serum of cattle and goats, sheep as well as 16 control reference sera.